Policy for Enhancing the Four Noble Truths Implementation of Thai Buddhists - Prueksamas, Budsara Girdwichai; Dockthaisong, Boonton; Ngamsnit, Sman (Research and Development Journal Suan Sunandha Rajabhat University, 2019)
Religion plays a very important part in Thai society. The main religion in Thailand is Buddhism. Buddhism is a religion of practice. This means that in order to derive benefit from the religion, one needs to exert oneself and put it into practice. Understanding is a part of every stage of the Buddhist path. Nowadays, Thai Buddhists filled Buddhism with such practices without understanding that the practices were not in the path of the Four Noble Truths, the practices endorsed by the Buddha. Public policy affects the lives of citizens in the whole country. It is issued by the government in order to solve problems, to promote the well-being of citizens, and to fulfill the basic needs of people. There is no doubt that if the government formulated policy for enhancing more Thai Buddhists to obtain the right understanding and earnestly practicing the Four Noble Truths, which were endorsed by the Buddha, many of the problems Thailand now faces could be satisfactorily solved or alleviated So, this research aimed to study that a Buddhist policy for Thailand to enhance implementation of the Four Noble Truths for Thai Buddhists, whether those policies are successes or failures, and what are the factors affecting the Four Noble Truths implementation of Thai Buddhists. Consequently, to fill in this practical gap, the present study intended to screen the data gathered on the effect of the attitude toward Buddhism, parental religious socialization, knowledge, and understanding of the Four Noble Truths concerning the implementation of the Four Noble Truths by Thai Buddhists. This was done in or order to provide guidelines for the formulation of policy for enhancing the implementation of the Four Noble Truths by Thai Buddhists.